Extracellular vesicles of U937 macrophage cell line infected with DENV-2 induce activation in endothelial cells EA.hy926 (2020)
Endothelial activation and alteration during dengue virus (DENV) infection are multifactorial events; however, the role of extracellular vesicles (EVs) in these phenomena is not known. In the present study, we characterized the EVs released by DENV-2 infected U937 macrophage cell line and evaluated the changes in the physiology and integrity of the EA.hy926 endothelial cells exposed to them. U937 macrophages were infected, supernatants were collected, and EVs were purified and characterized. Then, polarized endothelial EA.hy926 cells were exposed to the EVs for 24 h, and the transendothelial electrical resistance (TEER), monolayer permeability, and the expression of tight junction and adhesion proteins and cytokines were evaluated. The isolated EVs from infected macrophages corresponded to exosomes and apoptotic bodies, which contained the viral NS3 protein and different miRs, among other products. Exposure of EA.hy926 cells to EVs induced an increase in TEER, as well as changes in the expression of VE-cadherin and ICAM in addition leads to an increase in TNF-α, IP-10, IL-10, RANTES, and MCP-1 secretion. These results suggest that the EVs of infected macrophages transport proteins and miR that induce early changes in the physiology of the endothelium, leading to its activation and eliciting a defense program against damage during first stages of the disease, even in the absence of the virus.